2021
DOI: 10.3389/fmed.2021.779413
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Serum Lipid Metabolism Promotes the Occurrence and Development of Diabetic Retinopathy Associated With Upregulated Circulating Levels of VEGF-A, VEGF-D, and PlGF

Abstract: Purpose: This study aims to explore the correlations of arteriosclerosis-associated plasma indices with various severity levels of diabetic retinopathy (DR) and to test the hypothesis that elevated circulating level of known angiogenic cytokines induced by hyperglycemia is associated with dyslipidemia on DR.Methods: This cross-sectional study consists of 131 patients with type 2 diabetes. The patients were categorized based on their DR status into those with no DR (diabetes mellitus, DM), non-proliferative dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 48 publications
0
23
1
Order By: Relevance
“…VEGFA is not only the most important inducer of vascular leakage, but also a key angiogenic factor ( Sharma, 2020 ). In a previous study, vegfa-flk-1 signaling has been shown to be the main mediator of endothelial cell mitosis, survival and microvascular permeability ( Zhang, et al, 2021 ), suggesting that VEGF can become an important target for the treatment of ocular diseases. Inhibition of HIF-1α in DR can reduce VEGF expression and inhibit neovascularization in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…VEGFA is not only the most important inducer of vascular leakage, but also a key angiogenic factor ( Sharma, 2020 ). In a previous study, vegfa-flk-1 signaling has been shown to be the main mediator of endothelial cell mitosis, survival and microvascular permeability ( Zhang, et al, 2021 ), suggesting that VEGF can become an important target for the treatment of ocular diseases. Inhibition of HIF-1α in DR can reduce VEGF expression and inhibit neovascularization in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria were described previously (16). The exclusion criteria were the following: coexistence of other retinal diseases including retinal vein occlusion, macular hole, macular pucker, age-related macular degeneration, and inherited retinal diseases; recent history of eye anterior or posterior segment surgery; ocular media opacity; and inability to tolerate examinations due to severe system diseases; patients on lipidlowering therapy or with history of lipid disorders were also excluded (16). Subjects with cardiovascular diseases including angina and stroke as well as other server system disorders were also excluded.…”
Section: Participants' Characteristicsmentioning
confidence: 99%
“…apoB/ apoA-I 2.7 (AUC: 0.60, sensitivity = 0.50, specificity = 0.6). API 2.24 (AUC: 0.75; sensitivity = 0.71, specificity = 0.52), AI 2.91 (AUC, 0.72; sensitivity = 0.63; specificity = 0.72), AIP (AUC 0.564; sensitivity = 0.607, specificity = 0.552) were selected as the cutoff value as we described previously (16).…”
Section: Criteria Of Dyslipidemiamentioning
confidence: 99%
See 1 more Smart Citation
“…The differential regulation mechanism and the interactions between apos and lipid profiles remain uncertain. Our previous studies have shown that abnormal plasma levels of apolipoproteins and lipid profiles are correlated with variety of retinal vascular disorders including diabetic retinopathy (17)(18)(19). It is interesting to determine if apolipoprotein-mediated differential regulation of lipid metabolism is a pathological cause of the clinical phenotypes of nAMD and PCV.…”
Section: Introductionmentioning
confidence: 99%